2018
DOI: 10.1111/1462-2920.14285
|View full text |Cite
|
Sign up to set email alerts
|

Bloom of a denitrifying methanotroph, ‘Candidatus Methylomirabilis limnetica’, in a deep stratified lake

Abstract: Methanotrophic bacteria represent an important biological filter regulating methane emissions into the atmosphere. Planktonic methanotrophic communities in freshwater lakes are typically dominated by aerobic gamma-proteobacteria, with a contribution from alpha-proteobacterial methanotrophs and the NC10 bacteria. The NC10 clade encompasses methanotrophs related to 'Candidatus Methylomirabilis oxyfera', which oxidize methane using a unique pathway of denitrification that tentatively produces N and O from nitric … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
53
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(59 citation statements)
references
References 100 publications
0
53
1
Order By: Relevance
“…Aerobic CH 4 -oxidising microorganisms have long been recognised to play an important role in the regulation of CH 4 emissions to the atmosphere (Graf et al 2018). However, in the recent years, anaerobic oxidation of CH 4 (AOM) has been shown to be more widespread than previously predicted in areas of high organic matter availability (Evans et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Aerobic CH 4 -oxidising microorganisms have long been recognised to play an important role in the regulation of CH 4 emissions to the atmosphere (Graf et al 2018). However, in the recent years, anaerobic oxidation of CH 4 (AOM) has been shown to be more widespread than previously predicted in areas of high organic matter availability (Evans et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…3B and Supporting Information Fig. S3B; Text S3) may indicate obligate anaerobic methane oxidation coupled with nitrogen oxide reduction (Haroon et al, 2013;Graf et al, 2018).…”
Section: Unexpected Geomicrobiological Features In the Geochemical Prmentioning
confidence: 99%
“…Despite growing evidence that anaerobic methanotrophs play an important role in removing methane from lake ecosystems and reducing fluxes to the atmosphere, our knowledge about the microorganisms that perform AOM, particular within lake sediments, is still rudimentary. So far, only a few studies have identified freshwater AOM‐mediating microorganisms (Ettwig et al , ; Schubert et al ; Haroon et al ; Weber et al ; Graf et al ; Versantvoort et al ). In freshwater lake sediments, methanotrophic bacteria related to Candidatus Methylomirabilis oxyfera have been reported to perform methane oxidation coupled to denitrification (Deutzmann et al ), and archaea within the phylum Euryarchaeota possibly carried out sulfate‐ and/or iron‐dependent AOM (Schubert et al ; Weber et al ).…”
mentioning
confidence: 99%